ANALISIS PENGUKURAN KINERJA DENGAN BALANCED SCORECARD - Fabian, Muhammad Rauf; Prabandari, Sri Palupi (Jurnal Kewirausahaan dan Inovasi, 2023)
Performance is often still measured from a financial perspective, even though financial performance is heavily influenced by non-financial factors. The purpose of this study was to describe and analyze the performance of Siti Aisyah Madiun Islamic Hospital based on 4 perspectives of Kaplan & Norton's Balance Scorecard (1996). This type of research is descriptive quantitative. The data were obtained from documents, a survey of 65 outpatients and 240 employees, field observations, and consensus with the manager of Siti Aisyah Madiun Islamic Hospital. The results of the study show that the financial performance of the Siti Aisyah Madiun Islamic Hospital is not good in terms of operational cost control, the customer perspective performance is not good, the internal business process performance is good, and the overall growth and learning is good but the Siti Aisyah Madiun Islamic Hospital has not succeeded in controlling employee retention. The overall performance assessment of Siti Aisyah Madiun Islamic Hospital with a balanced scorecard based on four perspectives is in the good category. Performance appraisal with a balanced scorecard can be applied to non-profit organizations, especially Islamic-oriented hospitals.